Analisis Faktor yang Memengaruhi Pemilihan Tempat Persalinan Ibu Hamil di Wilayah Kerja Puskesmas Lasusua Kabupaten Kolaka Utara Tahun 2021 - Ferawati; Rahmawati Azis; Muhammad Syafar (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
Utilization of mothers giving birth in health facilities is very important, especially in preventing unwanted events during childbirth. The purpose of the study was to analyze the factors that influence the choice of place of delivery for pregnant women in the work area of the Lasusua Public Health Center, North Kolaka Regency. The type of research used is analytic survey research with a "cross-sectional study" (cross-sectional) design, with a population of 109 pregnant women, a sample of 57 people with purposive sampling technique and a questionnaire as a research instrument. The results obtained were knowledge (p value 0.000 < 0.05), culture (p value 0.002 < 0.05), pregnancy examination (p value 0.002 < 0.05), husband's support (p-value 0.001 < 0.05). ) and support from health workers p value 0.011 < 0.05 distance to health facilities (p value 0.556 > 0.05), infrastructure (p value 0.805 > 0.05) environmental comfort (p value 0.736 > 0 ,05). The results of the multivariate analysis of the support of health workers with the value of Exp (B) or OR are 165.9. The conclusion in this study is that knowledge, culture, antenatal care, husband's support, support from health workers have an influence while distance, infrastructure, environmental comfort, have no effect.